Crisis Management : Challenges and Responses - Singh, Chandrama (New Delhi, India Random Publications, 2016)
A crisis can occur as a result of an unpredictable event or as an unforeseeable consequence of some event that had been considered a potential risk. In either case, crisis almost invariably require that decisions be made quickly to limit damage to the organization. For that reason, one of the first actions in crisis management planning is to identify an individual to serve as crisis manager.
Include Bibliography and Index
Keywords: Crisis management -- Concepts and process of risk management